2020
DOI: 10.1002/jdd.12043
|View full text |Cite
|
Sign up to set email alerts
|

Most surface learning in the third year: Dental student learning approaches and implications for curriculum and assessment

Abstract: Context Dental schools seek to educate students to become inclined toward self‐directed, lifelong learning, an important mindset for healthcare professionals that may be linked to deep versus surface learning approaches. Students using a deep learning approach are more intrinsically motivated and actively engage in higher‐order thinking, while those using a surface learning approach are more extrinsically motivated and aim for passive learning. Objectives Because student learning approaches can be influenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
1
7
0
Order By: Relevance
“…The decrease in study motivation was highest in year 2 students. These findings complement earlier empirical research indicating that undergraduate students adopted a different learning approach and a sharp decrease in intrinsic motives with the entry to clinical training ( Wickramasinghe and Samarasekera, 2011 ; Lee et al, 2020 ). The curriculum structure of iMED allows the intermediate examination after the third semester.…”
Section: Discussionsupporting
confidence: 88%
“…The decrease in study motivation was highest in year 2 students. These findings complement earlier empirical research indicating that undergraduate students adopted a different learning approach and a sharp decrease in intrinsic motives with the entry to clinical training ( Wickramasinghe and Samarasekera, 2011 ; Lee et al, 2020 ). The curriculum structure of iMED allows the intermediate examination after the third semester.…”
Section: Discussionsupporting
confidence: 88%
“…The background of these results could be the structure of the undergraduate medical curriculum with predominantly preclinical subjects, which can be more easily studied with the help of presentations with audio recordings, and few practical training in the first year (Chenot, 2009;Hense et al, 2021;Rheingans et al, 2019). Furthermore, prior research among undergraduate medical and dental students found that students adopted a different learning approach (Lee at al., 2020;Wickramasinghe and Samarasekera, 2011) and increased levels of stress (Erschens et al, 2018) with the entry to clinical training. This might account for our findings that second year students (fourth semester) agreed most to negative aspects of digital teaching, and disagreed most to positive aspects of digital teaching, respectively.…”
Section: The Role Of Sample Characteristicsmentioning
confidence: 99%
“…Such career-long learning is crucially dependent on developing a capacity for effective self-reflection—the professional needs to be able to identify and appraise their learning needs. In dental education, as in the training of other professions, one major aim of teachers is to assist their students to become self-directed healthcare professionals and to initiate a lifelong learning process [ 1 ]. Students are seen as self-directed and active partners in their educational environment and should develop trusting relationships with their teachers [ 2 ].…”
Section: Introductionmentioning
confidence: 99%